Diversity, Distribution and Biomass of Tree Community in a Tropical Dry Forest of Northern Sri Lanka - Thirukkumaran, S.; Jeyavanan, K.; Sivachandiran, S. (University of Jaffna, 2017)
A study was conducted in a tropical dry forest in Northern Province of Sri Lanka. The study aims to assess the tree diversity, distribution and carbon stock. Field assessment was conducted in six sites of the state forest, namely Kulamurippu-A, Kulamurippu-B, Puthukudiyirupu, Nagansolai, Andankulam and Theravil. Sampling plots were randomly selected from each location at a size of 20 m × 20 m with three replicates. Samples were collected and herbarium specimens were prepared and submitted to the National Herbarium, Royal Botanical Garden, Peradeniya for species identification. Indices of Shannon−Wiener, evenness, species richness and IVI were used to assess the diversity and dominance of the species. Height and diameter of trees were measured to estimate biomass and carbon stock by using a tropical allometric equation. A total of 321 trees, comprising 31 species and six lianas from 20 families, were enumerated. The most representative family was ebenaceae with three species. The evaluated community presents an average density of 446 trees ha-1 and a basal area of 0.13 m2 ha-1. The based on the Importance Value Index (IVI), the forest was dominated by Drypetes sepearia (Wight & Arn.) Pax & Hoffm. (39.42 %), Manilkara hexandra (Roxb.) Dubard (38.19 %), followed by Chloroxylon swietenia DC (27.88 %), Diospyros ebenum Koenig (25.38 %). and Vitex altissimamilla L. f. (24.39 %). These five species account for 155.26 % of IVI. Mean Shannon diversity index and evenness were 1.94±0.11 and 0.91±0.01, respectively. This suggested that tree species were equally distributed with medium species diversity compared to wet forest. Mean carbon stock of the forest reserve was 206.34±19.12 Mg C ha-1, which was higher than other dry zone forests (92.62 Mg C ha-1) and lower than wet zone forest (336.8 Mg ha-1) in Sri Lanka. According to the IUCN red listed data, identified species were recorded as vulnerable (VU), near threaten (NT), endangered (EN), and least conservation (LC). Results of this study provide baseline information for formulation of conservation and management guidelines of forest ecosystems in the region.
Keywords: Diversity indices; Dry zone; IVI; Prevalence; State forest; Tropical forest